2014
DOI: 10.14411/eje.2014.082
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying predation pressure along an urbanisation gradient in Denmark using artificial caterpillars

Abstract: Abstract. Urbanisation results in a marked modification of habitats and influences several ecological processes, some of which give rise to beneficial ecological services. Natural pest control, the effect of predators on prey is one of such services. We quantified changes in the incidence of predation with increasing levels of urbanisation using artificial caterpillars made of green plasticine. Potential predators can be identified by the "attack marks" they leave on these artificial caterpillars. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 38 publications
6
63
1
Order By: Relevance
“…Although the latter result is in line with Ferrante et al. (), its explanatory power is low as indicated by the wide credible intervals (Figure g,h). Nevertheless, taken together, such findings may suggest that two communities of ground‐dwelling predatory arthropods with contrasting habitat preferences might have driven the observed pattern (Figure g,h).…”
Section: Discussionsupporting
confidence: 89%
“…Although the latter result is in line with Ferrante et al. (), its explanatory power is low as indicated by the wide credible intervals (Figure g,h). Nevertheless, taken together, such findings may suggest that two communities of ground‐dwelling predatory arthropods with contrasting habitat preferences might have driven the observed pattern (Figure g,h).…”
Section: Discussionsupporting
confidence: 89%
“…We found that contrary to expectation, invertebrate predation increases from the Equator to the poles (H4 not supported), but the apparent increase at higher latitude is greatly influenced by data from a single study in Denmark (Ferrante et al ., ) that may or may not be typical of the situation in northern temperate forests. Further records are required, and geographical gaps have to be filled.…”
Section: Discussionmentioning
confidence: 99%
“…We found a positive correlation between total and chewing insect predation rates and live plant ground cover (H5 supported). Ground cover is important for soil surface‐active arthropods (Magura, ), which are probably a key group attacking artificial caterpillars (Ferrante et al., ; Mansion‐Vaquié et al., ), and which are abundant in chaco serrano (E. González, personal observation). Plant material affects soil pH, humidity, and organic content (Sadler, Small, Fiszpan, Telfer, & Niemela, ), and it is usually preferred by invertebrates to bare ground.…”
Section: Discussionmentioning
confidence: 99%